State Repression, Exit, and Voice - Mathias Bühler; Andreas Madestam (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
What is the political legacy of state repression? Using local variation in state repression during the Khmer Rouge genocide in Cambodia, we investigate the effects of repression on political beliefs and behavior. We find that past state repression decreases votes for an authoritarian incumbent while enhancing electoral competition and support for democratic values four decades later. At the same time, individuals become more cautious in their interactions with the local community: they exhibit less trust, participate less in community organizations, and engage less with local government. Our theoretical model suggests that these opposing forces arise because experiencing repression bolsters preferences for pluralism while also heightening the perceived cost of dissent. Consequently, citizens are more likely to support the opposition in elections (voice) but engage less in civil society (exit) to avoid publicly revealing their political views. Exploring channels of persistence, we demonstrate that repression cultivates a lasting fear of violence as a societal threat, and that genocide memorials and remembrance ceremonies maintain the collective memory of the atrocities.
Keywords: D7; N4; O1; 330; state repression; political beliefs and behavior; collective memory; state-society relations